A preparation method and application of a lignin aqueous composite battery binder and its silicon-based negative electrode sheet

By using lignin aqueous battery binder in lithium-ion batteries, combining the dynamic disulfide bonds of polyacrylic acid and sulfonated lignin with sodium lipoate, the volume expansion and binder of silicon-based anode material are solved. Toxicity issues improve the battery's circulation performance and stability.

CN116014079BActive Publication Date: 2025-01-07GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310001662.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-03
Publication Date
2025-01-07
Estimated Expiration
2043-01-03

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based negative electrode material in existing lithium-ion batteries during the deintercalation process leads to cracking of the active material and unstable electrical contact. The traditional adhesive lacks mechanical strength, poor adhesion and high toxicity, which cannot meet the high energy density and The need for long life.

Method used

Using a lignin-based aqueous battery binder, a high-temperature dry and hot-esterified silicon-based negative electrode sheet is formed by mixing polyacrylic acid, sulfonated lignin and sodium lipoate with silicon-based active materials and conductive agents, and a covalent ester bond is used. and dynamic disulfide bonds provide strong mechanical strength and stress dissipation.

Benefits of technology

The high peel strength and strong adhesion of the silicon-based negative electrode sheet are achieved, and the volume expansion is effectively suppressed, the circulation performance and battery stability are improved, the use of organic solvents is avoided, and the toxicity is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116014079B_ABST
    Figure CN116014079B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a preparation method and application of a lignin aqueous composite battery binder and its silicon-based negative electrode sheet. The binder of the silicon-based negative electrode sheet of the present invention is a three-component aqueous composite binder of polyacrylic acid PAA, sulfonated lignin SL, and polythioic acid sodium PTA-Na. The PAA / SL / TA-Na solution is first prepared, and then the silicon-based active material and the conductive material are added to mix to obtain the negative electrode slurry, and finally coated on the substrate and polymerized and dried at high temperature to obtain the negative electrode sheet. The covalent bond-dynamic bond in the lignin aqueous composite binder of the present invention can provide strong mechanical strength to inhibit the volume expansion of the silicon-based material, and can dissipate stress through the reversible fracture and repair of the dynamic bond at the same time, effectively alleviating the volume effect of the silicon-based negative electrode, and solving the technical problem of poor cycle performance of the silicon-based negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to a preparation method and application of a lignin aqueous composite battery binder and a silicon-based negative electrode sheet thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have become important energy storage devices for portable devices such as mobile phones, laptops, and cameras. As people's requirements for high-power energy storage devices continue to increase, the current graphite-based carbon negative electrode materials for lithium-ion batteries can no longer meet the use requirements of high energy density and high power density. In terms of new lithium-ion battery negative electrode materials, the theoretical specific capacity of silicon negative electrode materials is as high as 4200mAh / g, which is 11 times that of traditional graphite negative electrodes (372mAh / g). In addition, due to its abundant resources and low cost, silicon negative electrode materials have become the most promising next-generation high-energy density lithium-ion battery negative electrode materials. Among them, silicon oxide is considered to be a very promising silicon-based negative electrode material for lithium-ion batteries. Compared with silicon, it has smaller expansion and a theoretical specific capacity of 2043mAh / g. However, there are still some problems in the practical application of silicon-based negative electrodes. The silicon-based negative electrode will undergo a huge volume expansion during the process of lithium insertion and extraction, causing the active material to break and pulverize and the active components to fall off from the current collector, thereby affecting the battery's coulombic efficiency, cycle and rate performance.

[0003] At present, the above problems can be improved by changing the size of silicon-based materials, hybrid composite materials, and designing new binders, but designing binders is one of the most convenient and economical methods. The role of the binder is to maintain the close connection between the active material, the conductive agent and the current collector, and to maintain the integrity of the electrode. Traditional binders are mainly linear polymers with rich polar groups, but this means that there are few interaction sites between the binder and the silicon-based material, which is difficult to withstand the stress caused by the volume expansion of the silicon-based material, resulting in cracking and crushing of the active material, poor electrical contact, and unstable SEI growth. Moreover, most of the existing binders are mainly based on highly polar solvents, such as N-methylpyrrolidone, N, N-dimethylamide, dimethyl sulfoxide, etc. The highly polar solvents are highly toxic, and the preparation of cross-linked network binders is complicated, which is not conducive to large-scale application. However, correspondingly, water-based binders also have the problems of insufficient mechanical strength, poor adhesion, and poor effect of inhibiting the expansion of silicon-based materials, which cannot meet the needs of lithium-ion batteries with high energy density, high capacity and long life. Therefore, it is necessary to develop a water-based binder with high mechanical strength, strong adhesion and good effect of inhibiting the expansion of silicon-based materials, so as to achieve excellent cycle stability of lithium-ion batteries using the silicon-based negative electrode sheet. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, an object of the present invention is to provide a lignin aqueous battery binder; another object of the present invention is to provide a silicon-based negative electrode sheet based on the lignin aqueous battery binder; another object of the present invention is to provide the application of the silicon-based negative electrode sheet in a lithium-ion battery.

[0005] To achieve the above object, the present invention is implemented by the following technical solutions:

[0006] The present invention provides a silicon-based negative electrode sheet based on a lignin aqueous battery binder, characterized in that the silicon-based negative electrode sheet comprises a silicon-based active material, a lignin aqueous battery binder and a conductive agent, and the lignin aqueous battery binder comprises polyacrylic acid, sulfonated lignin and sodium polylipoic acid.

[0007] The present invention also provides a method for preparing the above-mentioned silicon-based negative electrode sheet based on the lignin aqueous battery binder, which is characterized in that it includes the following steps: dissolving polyacrylic acid, sulfonated lignin, sodium thioctic acid, silicon-based active materials and conductive materials in water, mixing them evenly to obtain negative electrode slurry, then scraping the negative electrode slurry on a substrate, and finally drying and thermally esterifying at high temperature to obtain a negative electrode sheet.

[0008] Preferably, the mass ratio of the polyacrylic acid, sulfonated lignin and sodium lipoate is (1-100):1:1.

[0009] Preferably, based on the amount of raw materials of the lignin aqueous electrode binder composed of polyacrylic acid, sulfonated lignin and sodium lipoic acid, the amount of water used is 30 mL / g.

[0010] Preferably, the preparation method of the polyacrylic acid is: dissolving acrylic acid in water and then adding ammonium persulfate initiator, stirring continuously at 60° C. for 12 hours, washing the obtained polymer 2 to 3 times after the reaction is completed to remove unreacted monomers and initiator, and drying the obtained polyacrylic acid at 50° C. to remove moisture.

[0011] Preferably, the raw materials of the lignin aqueous battery binder are composed of polyacrylic acid, sulfonated lignin and sodium thioctic acid, and the active material, conductive material and the raw materials of the lignin aqueous battery binder are mixed in a mass ratio of (6-7):(1-2):(1-2), the silicon-based active material is at least one of silicon, silicon monoxide and silicon-carbon composite materials, and the conductive material is conductive carbon black.

[0012] Preferably, the mixing is carried out by continuous stirring at 30 to 1000 rpm for 1 to 10 hours.

[0013] Preferably, the negative electrode slurry has a concentration of 1.0 to 2.5 mg / cm 2 The active material surface loading is coated on a substrate, which is a copper foil substrate.

[0014] Preferably, the high temperature drying thermal esterification is vacuum drying at 150-200°C.

[0015] The present invention also provides the silicon-based negative electrode sheet based on the lignin aqueous battery binder for use in preparing lithium-ion batteries.

[0016] The lignin aqueous battery binder of the present invention can also be used to prepare positive electrode sheets or negative electrode sheets of other batteries.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention discloses a method for preparing a silicon-based negative electrode sheet based on a lignin aqueous battery binder. First, polyacrylic acid, sulfonated lignin, sodium thioctic acid, silicon-based active materials and conductive materials are dissolved in water, mixed evenly to obtain a negative electrode slurry, and then the negative electrode slurry is scraped onto a substrate, and finally dried and esterified at high temperature to obtain a negative electrode sheet. The preparation method uses water-soluble materials, avoids the use of organic solvents, and has low toxicity and is environmentally friendly. The present invention utilizes the polyhydroxyl groups of lignin and the carboxyl groups of polyacrylic acid to form a covalent ester bond to obtain a rigid three-dimensional structure, and then introduces the dynamic disulfide bond of flexible sodium polythioctic acid, and the hydrogen bond formed between the carboxyl group and the hydroxyl group of lignin to form a double dynamic bond; the covalent bond-dynamic bond combination can provide strong mechanical strength to inhibit the volume expansion of the silicon-based material when the volume expands, and at the same time, stress dissipation is performed by breaking and repairing the dynamic bond. The peel strength of the silicon-based negative electrode sheet based on the lignin aqueous binder of the present invention reaches 4.9N, has strong adhesion, and effectively suppresses the volume effect of the silicon-based negative electrode sheet during charging and discharging, thereby improving the cycle performance of the silicon-based negative electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a peel strength analysis diagram of silicon-based negative electrode sheets;

[0020] Figure 2 This is the cycling performance diagram of the silicon oxide negative electrode half-cell at a current density of 0.2A / g. DETAILED DESCRIPTION

[0021] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0022] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0023] Example 1 Preparation of silicon-based negative electrode sheet based on PAA / SL / TA-Na-150 binder

[0024] 1. Preparation of polyacrylic acid (PAA): 10 ml of acrylic acid (AA) was measured and placed in a reaction bottle containing 100 ml of water, and 0.01 g of ammonium persulfate initiator was added. The mixture was stirred at 60° C. for 12 h. After the reaction, the obtained polymer was washed with anhydrous ethanol for 3 times to remove unreacted monomers and initiator. The obtained polyacrylic acid was dried at 50° C. in a blast drying oven to remove moisture, and then dried for later use.

[0025] 2. Preparation of sodium thioctic acid (TA-Na): 5 g of thioctic acid was measured and then added into a sodium hydroxide-anhydrous ethanol solution (the molar ratio of thioctic acid to sodium hydroxide was 1:1.2). After the reaction generated a precipitate, the precipitate was washed with anhydrous ethanol for several times and then dried to obtain sodium thioctic acid;

[0026] 3. Preparation of silicon-based negative electrode sheet: 0.02 g of the obtained polyacrylic acid, sulfonated lignin and sodium thioctic acid were weighed and mixed in 600 μL of deionized water in a mass ratio of 1:1:1 to prepare a PAA / SL / TA-Na solution, and then 0.14 g of silicon oxide with a ball-milled particle size of 500 nm and 0.04 g of conductive carbon black were added, and then stirred at a speed of 800 rpm for 10 h to mix the slurry. The mixed slurry was heated to 1.5 mg / cm 2 The active material loading is evenly coated on the copper foil and dried at 150℃ for 10h to make the components undergo thermal esterification to obtain the pole piece. Sodium thioctic acid will polymerize to form polysodium thioctic acid during the thermal esterification process. The dried pole piece is cut into a disc with a diameter of 14mm as the negative pole piece of the button battery.

[0027] Comparative Example 1 Preparation of silicon-based negative electrode sheet based on PAA / SL / TA-Na-60 binder

[0028] The preparation methods of PAA and TA-Na were the same as those in Example 1. Preparation of silicon-based negative electrode sheets: 0.02 g of the obtained polyacrylic acid, sulfonated lignin, and sodium thioctic acid were weighed and mixed in 600 μL of deionized water in a mass ratio of 1:1:1 to prepare a PAA / SL / TA-Na solution, and then 0.14 g of ball-milled silicon dioxide and 0.04 g of conductive carbon black were added, and then stirred at a speed of 800 rpm for 10 h to mix the slurry. The mixed slurry was heated to 1.5 mg / cm 2 The active material loading amount was evenly coated on the copper foil and dried at 60°C for 10 hours to obtain the electrode. The dried electrode was cut into a disc with a diameter of 14 mm as the negative electrode of the button battery.

[0029] Comparative Example 2 Preparation of silicon-based negative electrode sheet based on PAA / SL-150 binder

[0030] The preparation method of PAA is the same as that of Example 1. Preparation of silicon-based negative electrode sheet: 0.02 g of the obtained polyacrylic acid and sulfonated lignin were weighed and mixed in 600 μL of deionized water in a mass ratio of 1:1 to prepare a PAA / SL solution, and then 0.14 g of ball-milled silicon dioxide and 0.04 g of conductive carbon black were added, and then stirred at a speed of 800 rpm for 10 h to mix the slurry. The mixed slurry was heated to 1.5 mg / cm 2 The active material loading is evenly coated on the copper foil, and then dried at 150℃ for 10h to obtain the electrode. The dried electrode is cut into a disc with a diameter of 14mm as the negative electrode of the button battery.

[0031] Comparative Example 3 Preparation of silicon-based negative electrode sheet based on PAA / SL-60 binder

[0032] The preparation method of PAA is the same as that of Example 1. Preparation of silicon-based negative electrode sheet: 0.02 g of the obtained polyacrylic acid and sulfonated lignin were weighed and mixed in 600 μL of deionized water in a mass ratio of 1:1 to prepare a PAA / SL solution, and then 0.14 g of ball-milled silicon dioxide and 0.04 g of conductive carbon black were added, and then stirred at a speed of 800 rpm for 10 h to mix the slurry. The mixed slurry was heated to 1.5 mg / cm 2 The active material loading amount was evenly coated on the copper foil and dried at 60°C for 10 hours to obtain the electrode. The dried electrode was cut into a disc with a diameter of 14 mm as the negative electrode of the button battery.

[0033] Comparative Example 4 Preparation of silicon-based negative electrode sheet based on PAA binder

[0034] The preparation method of PAA is the same as that of Example 1. Preparation of silicon-based negative electrode sheet: 0.02 g of the obtained polyacrylic acid was weighed and mixed with 600 μL of deionized water to prepare PAA solution, and then 0.14 g of silicon dioxide and 0.04 g of conductive carbon black were added, and then stirred at a speed of 800 rpm for 10 h to mix the slurry. The mixed slurry was heated to 1.5 mg / cm 2 The active material loading amount was evenly coated on the copper foil and dried at 60°C for 10 hours to obtain the electrode. The dried electrode was cut into a disc with a diameter of 14 mm as the negative electrode of the button battery.

[0035] Example 1 Performance Characterization of Silicon-Based Anode Sheet and Half-Cell

[0036] 1. Adhesion test

[0037] The silicon-based negative electrode sheets of Example 1 and Comparative Examples 1 and 4 were fixed on a peeling force tester, and then subjected to a 180-degree peeling test at a speed of 10 mm / min. The peeling test results are shown in FIG. Figure 1As shown, the average peel strength of Example 1 reached 4.9N, which is higher than 3.5N of Comparative Example 4 and 2.5N of Comparative Example 1. This shows that after the binder of Example 1 is esterified at high temperature, the esterification degree of polyacrylic acid and sulfonated lignin is significantly improved, which strengthens the adhesion of the network, can maintain the integrity of the electrode during the battery cycle, and closely connect the active material, conductive material and copper foil current collector. However, Comparative Example 1 has not been completely esterified, the esterification degree is low, and the adhesion is weak; Comparative Example 4 has only a single-component PAA binder, and the adhesion effect is not as good as that of Example 1.

[0038] 2. Cycling performance characterization of silicon-based negative electrode half-cell at a current density of 0.2A / g

[0039] Assembly of half-cell: Silicon-based negative electrode sheets with a diameter of 14 mm were assembled into lithium-ion half-cells in a glove box filled with argon and with a water and oxygen content of less than 0.1 ppm. The electrolyte system selected an EC / DEC (v / v=1:1) solution containing 10 wt% FEC and 1 wt% VC, and the separator used a commercial polypropylene porous membrane.

[0040] The cycling performance of each half-cell at a current density of 0.2 A / g is characterized as follows Figure 2 As shown, after 100 cycles, the half-cell of Example 1 still retains a discharge capacity of 1192 mAh / g, which is better than that of Comparative Example 2. This shows that the addition of sodium thioctic acid can achieve the breaking and repair of dynamic bonds for stress dissipation, and enhance the inhibitory effect on the expansion of silicon-based materials. The cycle performance of Example 1 and Comparative Example 2 is better than that of Comparative Example 4, indicating that the polyhydroxy three-dimensional structure of lignin itself is esterified and cross-linked with the carboxyl group of polyacrylic acid to obtain a rigid three-dimensional structure, which can provide strong mechanical strength to inhibit the volume expansion of silicon-based materials when the volume expands. However, Comparative Examples 1 and 3 have poor cycle performance because of their low degree of esterification and cannot inhibit expansion.

[0041] The above two tests show that PAA / SL / TA-Na aqueous polymer binder forms a covalent bond-dynamic bond network through high-temperature thermal esterification, which can provide strong mechanical strength to inhibit the volume expansion of silicon-based materials, and can also dissipate stress through the breaking and repair of dynamic bonds. The application of this binder to the silicon-based negative electrode of lithium-ion batteries can effectively inhibit the volume effect of the electrode cycle process and significantly improve the battery's cycle performance.

[0042] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A silicon-based negative electrode sheet based on lignin aqueous battery binder, characterized in that: The silicon-based negative electrode sheet comprises a silicon-based active material, a lignin aqueous battery binder and a conductive agent, wherein the lignin aqueous battery binder comprises polyacrylic acid, sulfonated lignin and sodium thioctic acid, and the mass ratio of the polyacrylic acid, sulfonated lignin and sodium thioctic acid is (1-100):1:1; The method for preparing the silicon-based negative electrode sheet comprises the following steps: The preparation method of the polyacrylic acid is as follows: dissolving acrylic acid in water, adding ammonium persulfate initiator, stirring continuously at 60° C. for 12 hours, washing the obtained polymer 2 to 3 times after the reaction is completed to remove unreacted monomers and initiator, and drying the obtained polyacrylic acid at 50° C. to remove moisture; Dissolve polyacrylic acid, sulfonated lignin, sodium thioctic acid, silicon-based active material and conductive agent in water, mix them evenly to obtain negative electrode slurry, then scrape the negative electrode slurry on a substrate, and finally dry and heat esterify at high temperature to obtain a negative electrode sheet, wherein the high temperature drying and heat esterification is vacuum drying at 150-200°C; polyacrylic acid, sulfonated lignin and sodium thioctic acid are used to form the raw materials of lignin aqueous battery binder, the raw materials of silicon-based active material, conductive agent and lignin aqueous battery binder are mixed in a mass ratio of (6-7):(1-2):(1-2), the silicon-based active material is at least one of silicon, silicon oxide and silicon-carbon composite material, and the conductive agent is conductive carbon black.

2. The silicon-based negative electrode sheet based on lignin aqueous battery binder according to claim 1, characterized in that: The mixing is carried out by continuous stirring at 30-1000 rpm for 1-10 hours.

3. The silicon-based negative electrode sheet based on lignin aqueous battery binder according to claim 1, characterized in that: The negative electrode slurry has a concentration of 1.0-2.5 mg / cm 2 The active material surface loading is coated on a substrate, which is a copper foil substrate.

4. The silicon-based negative electrode sheet based on the lignin aqueous battery binder according to any one of claims 1 to 3 is used in the preparation of lithium-ion batteries.

Citation Information

Patent Citations

  • Silicon-based negative electrode self-repairing polymer binder and preparation method and application thereof

    CN113054193A

  • Silicon-based negative plate and preparation method and application thereof

    CN114725313A